1999
DOI: 10.1345/aph.17216
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotics: Part II Adverse Effects, Drug Interactions, and Costs

Abstract: Risperidone or olanzapine are recommended as first-line agents for schizophrenia due to accumulating controlled trials and clinical experience. Quetiapine should be considered with partial response or if EPS develop, and clozapine is an option with treatment-refractory patients. Atypical agents may contribute to a better quality of life, but conventional neuroleptics are the first choice for strictly cost considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 40 publications
2
71
0
1
Order By: Relevance
“…probability of anti-Parkinsonian agent usage anti-Parkinsonian medication increased with increasing risperidone dose) indicated that risperidone was likely to be the reason for antiParkinsonian medication usage/EPS incidence. This is consistent with the reported dose-related EPS side effects of risperidone (Brown et al, 1999;Love and Nelson, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…probability of anti-Parkinsonian agent usage anti-Parkinsonian medication increased with increasing risperidone dose) indicated that risperidone was likely to be the reason for antiParkinsonian medication usage/EPS incidence. This is consistent with the reported dose-related EPS side effects of risperidone (Brown et al, 1999;Love and Nelson, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Pretreatment with olanzapine completely eliminated cocaine self-administration in three of four subjects, and markedly suppressed responding to less than 10% of control rates in the fourth subject. Effective doses of olanzapine were within the therapeutic dose range for treatment of psychosis in humans (Brown et al, 1999;Albers et al, 2005). In separate experiments, substitution of olanzapine for cocaine failed to maintain self-administration behavior above saline extinction levels in any subject.…”
Section: Discussionmentioning
confidence: 82%
“…However, TAs are associated with diminished tolerability and patient compliance due in part to a high incidence of adverse extrapyramidal side effects including parkinsonism and tardive dyskinesia (Brown, Markowitz, Moore, & Parker, 1999;Dolder et al, 2002). TAs are reported to have only partial efficacy against negative, cognitive, and depressive symptoms of schizophrenia and are associated with patients' complaints of reduced quality of life (Csernansky & Schuchart, 2002;Naber et al, 2001).…”
Section: Introductionmentioning
confidence: 99%